Potential for Energy Savings in Educational Institutions in Ghana - Elvis Twumasi; Emmanuel Asuming Frimpong; Leslie Novihoho (Jurusan Teknik Elektro Universitas Andalas, 2019)
This paper presents the results of an energy audit carried out to assess the potential of energy savings in educational institutions in Ghana using the Kwame Nkrumah University of Science and Technology (KNUST) as the case study institution. It also outlines a simple and effective technique for such an audit. The College of Engineering; one of the six Colleges of KNUST was used as the study location. Light bulbs and fans at the classrooms, corridors, laboratories and washrooms were monitored for energy wastage. The monitoring period was one month. The energy wastage over the period was estimated to be 1718.24kWh, which is high. The yearly energy wastage at KNUST for the areas assessed is projected to be 95.276MWh, which is alarming. Urgent steps are therefore needed to curb this wastage.Keywords: Energy auditing, Energy efficiency, Energy efficiency measures, Energy saving and Energy wastage